A STUDY OF COLLOCATIONAL ERRORS IN INDONESIAN EFL LEARNERS’ ABSTRACT WRITING - Al Khansa Nova Misbahillah; Nurdin (JEELL (Journal of English Education, Linguistics and Literature), 2025)
This study aims to investigate the use of English collocations in abstracts of research articles written by Indonesian advanced learners. Thirty abstracts of research articles published in National Journals were taken as the data sources. Every collocation suspected as verb-noun lexical collocation was identified. The errors were analyzed using four different English dictionaries and BNC. The result showed that 46 out of 130 were unacceptable collocations. The types of unacceptable collocations found in this study were the wrong choice of verb, wrong choice of noun, Usage 1, Usage 2, preposition-related errors, article missing, the use of a singular noun instead of the plural one, and syntactic structure wrong. Findings also showed that errors produced by learners were attributed to their learning strategy, namely ignorance of rule restrictions, false concept hypothesized, use of synonyms, and approximation. In addition, the result also showed that learners’ use of collocation was influenced by their L1. The ignorance of rule restrictions seems to be the most frequently occurring. It can be concluded that the main causes of unacceptable collocations were errors in verb choice and the influence of the student's first language.